Progress on the Extraction, Separation, Biological Activity, and Delivery of Natural Plant Pigments - Xianwen Lu; Wenjun Li; Qi Wang; Jing Wang; Song Qin (Molecules, 2023)
Natural plant pigments are safe and have low toxicity, with various nutrients and biological activities. However, the extraction, preservation, and application of pigments are limited due to the instability of natural pigments. Therefore, it is necessary to examine the extraction and application processes of natural plant pigments in detail. This review discusses the classification, extraction methods, biological activities, and modification methods that could improve the stability of various pigments from plants, providing a reference for applying natural plant pigments in the industry and the cosmetics, food, and pharmaceutical industries.